PENGGUNAAN SURAT AL-FATIHAH TERHADAP PENGOBATAN ALTERNATIF "Kajian Living Qur’an: Studi Kasus Pengobatan Para Ustadz di Kota Palu" - Muhsin Alhaddar (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
This paper is a research study of authors who want to know the use of Surat Al-Fatihah as a medium for treatment. To study this the writer uses the study of the living Qur'an to see the phenomena that exist especially in the city of Palu. Basically the use of the letter Alfatihah as a means of treatment had occurred at the time of the Prophet, in this case it was once told by Abu Said al-Khudri who told that a Kabilah leader who recovered from a bite of canjengkik because he was treated with an Alfatihah Letter. Therefore Alfatihah is also named as al-Syifa which means healer. In this article the author wants to answer two issues, namely the foundation of the clerics in the use of the Alfatihah letter as a means of treatment and community reception of the Alfatihah Letter used by the Ustadz. To answer this the writer will use interview techniques to obtain more objective results. In the study of literature the author has compared with several works, so that there will not be plagiarism among the works that write such thing is the Alfatihah Psikologi Alfatihah sebagai Seolusi Kebahagiaan by Eko Hardi Ansyah, et al. Membaca Alfatihah Reflektif Intiutif Menurunkan Depresi dan Meningkatkan Imunitas, and several other works will be written in the previous studies. In its conclusion the authors explain that the Ustadz, Kanai or Habib know the function of the Alfatihah can be used as a means of treatment of their offspring and there are also those who automatically get it. This is influenced by their beliefs and the beliefs of patients.